VARIABILITY IN PERFORMANCE INDICATORS OF THE NETHERLANDS WOMEN’S NATIONAL HANDBALL TEAM AT THE 2019 WORLD CHAMPIONSHIP (Kinesiology, 2022)
The primary objective of this study was to discover the positional attack performance indicators of the winning Netherlands women’s national handball team during the 2019 World Championship in Japan. An ideographic, follow-up and multidimensional observational design was used to record and analyse positional attacks disputed in equal numbers of players (6v6) excluding attacks with an empty goal. Polar coordinates allowed us to determine behaviour patterns as well as performance indicators related to attack continuity, situations used to destabilise the opponents’ defence, and actions involved in completing the attack. Two levels of analysis were used: each match individually and all the team’s matches as a whole. Results show that each match had its own specific game dynamics as different behaviour patterns were activated and different performance indicators were observed depending on the match. These findings highlight the variability and dynamic nature of the offensive behaviours and performance indicators of the world champion team, emphasising the need to study performance indicators with research projects that respect that they are specific and changing.Key words: match analysis, behaviour patterns, polar coordinates analysis